Antenatally Diagnosed Renal Duplex Anomalies: Sonographic Features and Long-Term Postnatal Outcome - Sepulveda, W (John Wiley and Sons Ltd, 2011)
Objectives-The purpose of this study was to assess the diagnostic accuracy and infant outcomes of antenatally detected renal duplex anomalies. Methods-An observational longitudinal study of cases of renal duplex anomalies diagnosed on prenatal sonography was conducted. Information on the prenatal sonographic findings, antenatal course, and perinatal outcome was obtained by reviewing the sonography reports and delivery records. Postnatal follow-up, including neonatal and infant evaluations, was obtained from hospital records. Results-During a 7-year period, a total of 24 cases of renal duplex anomalies were identified prenatally. Three cases were excluded from subsequent analysis because of termination of pregnancy after the diagnosis of a severe brain abnormality, loss to follow-up, and an inability to confirm the prenatal diagnosis on neonatal renal sonography. Among the 21 confirmed cases, the presence of two separate renal pelvises was the most common prenatal sonographic feature (n = 15 [71%]), followed by dilatation of a single moiety with a dilated ipsilateral ureter or ureterocele (n = 6 [29%]). In 43% of cases, the renal duplex anomalies had no adverse associations, but in 48%, they were complicated by a urinary tract infection, and 48% of the infants required a surgical procedure during early childhood. Conclusions-Renal duplex anomalies can be accurately diagnosed by prenatal sonography even when there is minimal dilatation of the renal pelvis. Antenatal diagnosis allows planning of postnatal care, which may prevent urinary tract infections and renal function impairment. The natural history of antenatally diagnosed duplex anomalies seems to be overall benign, with urinary tract infections and the need for surgery being the most common complications in affected infants. © 2011 by the American Institute of Ultrasound in Medicine.